Advancing children's rights in detention : a model for international reform - Kilkelly, Ursula; Bergin, Pat (Bristol : Bristol University Press, 2022)
Drawing on Ireland's experience of transforming law, policy and practice and combining theory with real-life experiences, this compelling book demonstrates how a progressive rights-based approach to child detention can be implemented.
Previously issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on May 6, 2022).
Keywords: Children's rights; Juvenile detention; Politics and Government; Politics & government